Kegiatan Majelis Sholawat Diba’ Bersama IPNU IPPNU untuk Membentuk Karakter Religius Remaja di Desa Tropodo, Kecamatan Waru, Kabupaten Sidoarjo - Achmad Defri Juliansyah; Yuliastutik Yuliastutik (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Sholawat is a request to obtain blessings and respect for the Prophet Muhammad SAW. Sholawat diba' is a form of worship to get closer to Allah SWT. The Sholawat assembly was held in the community with the aim of increasing religious knowledge and belief, which in turn encourages the implementation of religious teachings as a way for the community to foster friendship between residents. Community service activities through Diba'an have succeeded in achieving an important goal, namely forming the religious character of Tropodo village. Not only that, this activity has also succeeded in increasing the spiritual values, social values ​​and cultural values ​​of the Tropodo village community. The Diba Sholawat Assembly activity held together with IPNU and IPPNU in Tropodo Village, Waru District, Sidoarjo Regency, has a significant role in shaping the religious character of teenagers. Through this activity, teenagers are not only trained to love and practice Islamic teachings, but also in the form of love for the Prophet Muhammad SAW